The Importance of Microcurrent Reflexology in the Treatment of Autism - Bakhtiyorovna, Azimova Zebo; Avazovna, Jamalova Shakhlo; Rakhimovich, Bafoyev Khayotjon (European Journal of Life Safety and Stability (2660-9630), 2021)
The objective of the present paper was to study the influence of micro current reflex therapy on the compromised speech functions in children (n = 84) presenting with cerebral palsy in comparison with the control group comprised of children (n = 56) with the same problems treated by medic mental therapy. The micro current reflex therapy was shown to be instrumental in the restoration of the compromised speech function. Moreover, it promoted positive dynamics of loco motor and cognitive disorders.